PENGARUH LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI PADA BADAN PENGELOLA PAJAK DAN RETRIBUSI DAERAH KOTA TASIKMALAYA - Setia Rachmanda, Yudi; Zulfikar Bintang Satrio, Muhamad; Agustian, Aldy; Riswandi, Dede (JURNAL EKONOMI PERJUANGAN, 2024)
This study examines the effect of the work environment on employee performance at the Regional Tax and Retribution Management Agency in Tasikmalaya City. A descriptive method with a quantitative approach was used, gathering data through interviews and questionnaires. Data analysis included validity testing via item analysis and product moment formula, reliability with Cronbach's Alpha, correlation coefficient, t-test, simple linear regression, F-test, and coefficient of determination. Results showed a very low correlation (-0.185) between the work environment (X) and employee performance (Y), which was not statistically significant. Regression analysis indicated that the work environment’s effect on performance is minor, as shown by Fcount < Ftable (1.50 < 3.96). The determination coefficient (Kd) was 34.22%, suggesting that 65.78% of employee performance is influenced by other factors.   Keywords: Work Environment and Employee Performance